PENGARUH KEBERADAAN TANGKAHAN TERHADAP PENDARATAN HASIL TANGKAPAN PELABUHAN PERIKANAN NUSANTARA SIBOLGA (Tangkahan Influence of Catch Landing in Sibolga Fishing Port) - Sahat Maruli Simatupang; Ernani Lubis (Bogor Agricultural University, 2012)
ABSTRACTFishing port which is an important infrastructure in the marine fisheries sector, need to be managed optimally so that its functions are fulfilled by existing provisions. However, in some areas, fishing ports function is hampered because many tangkahan are in around the location of the fishing port. This condition occurs as it does in the Territorial Fishing Port (PPN) of Sibolga and Belawan fishing port so the utilization is less than optimal. This study aims to determine the impact of tangkahan to the catch landing in Sibolga fishing port. The study was conducted in June-July 2009 in the five Tangkahan (UD Ilham, Sabena, Budi Jaya, Renta Sari, Sari Hope Sea) and Sibolga fishing port. This research was conducted by the case study method. The data are taken from primary and secondary. Primary data retrieved through observation and interviews with respondents: tangkahan owners, managers of Sibolga fishing port and fish quality measurement with organoleptic analysis. The analysis is done qualitatively and quantitative descriptive through the presentation of tables and graphs. The analysis showed that the presence of a negative impact on landed catch production in Sibolga fishing port. Production of Sibolga fishing port only 4.3 percent when compared with the production in tangkahan reaching 95.7 percent of total catch landed in the Teluk Tapian Nauli. Largest fishery business center is currently in many tangkahan not in Sibolga fishing port. The potential increase in the number of catches in Sibolga fishing port very large if all the ships could be transferred to this port. Comparison between the quality of the catch in Sibolga fishing port and tangkahan is very small (less than 1 scale) or the quality of the catch in both types of the landing site is almost the same.Keywords: impact, Sibolga fishing port, tangkahan——ABSTRAKPelabuhan perikanan merupakan prasarana penting pada sektor perikanan laut. Namun di beberapa daerah, fungsi pelabuhan perikanan terhambat karena banyaknya tangkahan yang berada di sekitar lokasi pelabuhan perikanan. Kondisi ini terjadi seperti halnya di Pelabuhan Perikanan Nusantara (PPN) Sibolga dan PPN Belawan sehingga pemanfaatannya kurang optimal. Penelitian ini bertujuan untuk mengetahui dampak tangkahan terhadap pendaratan hasil tangkap-an di PPN Sibolga. Penelitian dilakukan pada bulan Juni-Juli 2009 di lima tangkahan (UD Ilham, Sabena, Budi Jaya, Renta Sari, Harapan Sari Laut) dan PPN Sibolga. Penelitian ini dilakukan dengan metode studi kasus. Data yang diambil adalah primer dan sekunder. Data primer diambil melalui pengamatan dan wawancara kepada responden pemilik tangkahan, pengelola PPN Sibolga serta pengukuran mutu ikan secara organoleptik. Analisis dilakukan secara deskriptif kualitatatif dan kuantitaif melalui penyajian tabel dan grafik. Hasil analisis menunjukkan bahwa keberadaan tangkahan berpengaruh negatif terhadap produksi ikan yang didaratkan di PPN Sibolga. Produksi PPN Sibolga hanya 4,3 % apabila dibandingkan dengan produksi di tangkahan-tangkahan yang mencapai 95,7 % dari jumlah ikan didaratkan di Teluk Tapian Nauli. Pusat bisnis perikanan terbesar saat ini berada di tangkahan-tangkahan bukan di PPN Sibolga. Potensi peningkatan jumlah hasil tangkapan di PPN Sibolga sangat besar jika semua kapal bisa dialihkan ke pelabuhan ini. Perbandingan mutu hasil tangkapan di PPN Sibolga dan di tangkahan sangat kecil (kurang dari skala 1) atau mutu hasil